1997
DOI: 10.1021/bi9700781
|View full text |Cite
|
Sign up to set email alerts
|

Probing Contacts to the DNA Backbone in the trp Repressor−Operator Sequence-Specific Protein−Nucleic Acid Complex Using Diastereomeric Methylphosphonate Analogues

Abstract: Fourteen analogue DNA sequences containing the trp operator sequence and a single diastereomeric methylphosphonate linkage are each prepared from the stereochemically pure nucleoside methylphosphonate dimer building block, prepared as a phosphoramidite. The analogue sequences are shown to be single diastereomers on the basis of HPLC analysis of the digestion mixture; in each case, only a single diastereomeric dimer is present. These analogue sequences can be used effectively to probe for interactions to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…The methylphosphonate linkage, where one of the two nonbridging oxygens is replaced by a methyl group, was used to identify phosphate contacts in DNA-protein complexes (Noble et al+, 1984;Botfield & Weiss, 1994;Smith & McLaughlin, 1997)+ However, methylphosphonates have been used only rarely in studies of RNA-protein interactions, because the ribose methylphosphonate linkage is not chemically stable (Hamy et al+, 1993;Pritchard et al+, 1994)+ Although no enzymatic method exists for introduction of a methylphosphonate linkage, deoxynucleoside methylphosphonoamidites can be used to obtain a mixture of the two stereoisomers by chemical synthesis+ This mixture can easily be separated by HPLC when the oligomer is short (Hamy et al+, 1993;Lebedev et al+, 1993;Pritchard et al+, 1994)+ In contrast to the ethylated phosphate, the methylphosphonate modification is nearly isosteric with the phosphodiester linkage and therefore should not introduce any steric clashes with the protein or within the RNA+ Unlike the phosphorothioate substitution, the methylphosphonate linkage is uncharged, which neutralizes a small section of the RNA backbone (Fig+ 1A)+ This change in electrostatic potential can be expected to reduce the local water structure organization (Kulinska et al+, 1997) as well as weaken the ionic attraction between RNA and protein+ Therefore, the methylphosphonate linkage can be expected to be a useful phosphate analog, because the substitution of an oxygen by a methyl group should be drastic enough to disrupt protein-phosphate contacts and yet conservative enough to only locally disturb the RNA-protein interface+…”
Section: Introductionmentioning
confidence: 99%
“…The methylphosphonate linkage, where one of the two nonbridging oxygens is replaced by a methyl group, was used to identify phosphate contacts in DNA-protein complexes (Noble et al+, 1984;Botfield & Weiss, 1994;Smith & McLaughlin, 1997)+ However, methylphosphonates have been used only rarely in studies of RNA-protein interactions, because the ribose methylphosphonate linkage is not chemically stable (Hamy et al+, 1993;Pritchard et al+, 1994)+ Although no enzymatic method exists for introduction of a methylphosphonate linkage, deoxynucleoside methylphosphonoamidites can be used to obtain a mixture of the two stereoisomers by chemical synthesis+ This mixture can easily be separated by HPLC when the oligomer is short (Hamy et al+, 1993;Lebedev et al+, 1993;Pritchard et al+, 1994)+ In contrast to the ethylated phosphate, the methylphosphonate modification is nearly isosteric with the phosphodiester linkage and therefore should not introduce any steric clashes with the protein or within the RNA+ Unlike the phosphorothioate substitution, the methylphosphonate linkage is uncharged, which neutralizes a small section of the RNA backbone (Fig+ 1A)+ This change in electrostatic potential can be expected to reduce the local water structure organization (Kulinska et al+, 1997) as well as weaken the ionic attraction between RNA and protein+ Therefore, the methylphosphonate linkage can be expected to be a useful phosphate analog, because the substitution of an oxygen by a methyl group should be drastic enough to disrupt protein-phosphate contacts and yet conservative enough to only locally disturb the RNA-protein interface+…”
Section: Introductionmentioning
confidence: 99%
“…[7] It was recently demonstrated that modified oligonucleotides can also deliver precise information on protein functions and interactions with DNA provided that detailed information on their intrinsic structure is available. [8][9][10][11] The physicochemical and biological properties of modified oligonucleotides can be widely tuned since numerous procedures have been elaborated that enable various modifications to internucleotide phosphodiester bonds, sugar or base moieties. [12] Modification of the internucleotide phosphorus centre allows the synthesis of oligonucleotides with enhanced affinity towards complementary templates, increased enzymatic stability, and improved membrane permeability.…”
Section: Introductionmentioning
confidence: 99%
“…But even this interaction may only contribute minimally to target recognition since the symmetrical mutations of C ϩ9 ϪG Ϫ9 → G ϩ9 ϪC Ϫ9 has relatively little effect upon repressor binding monitored in vivo (7). A number of direct contacts to the phosphodiester residues are also present in the complex (5) that afford complex stabilization (8). In addition to these direct interactions, a number of water-mediated contacts are present involving both the base residues (5,9,10) and the internucleotide phosphates (5,8).…”
Section: Introductionmentioning
confidence: 99%
“…A number of direct contacts to the phosphodiester residues are also present in the complex (5) that afford complex stabilization (8). In addition to these direct interactions, a number of water-mediated contacts are present involving both the base residues (5,9,10) and the internucleotide phosphates (5,8). Base analogue studies have assisted in illustrating that such interactions contribute to high affinity binding in this complex (8,10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation